Surface‐2D/Bulk‐3D Heterophased Perovskite Nanograins for Long‐Term‐Stable Light‐Emitting Diodes. Issue 1 (18th November 2019) - Han, Tae‐Hee; Lee, Jin‐Wook; Choi, Yung Ji; Choi, Chungseok; Tan, Shaun; Lee, Sung‐Joon; Zhao, Yepin; Huang, Yu; Kim, Dongho; Yang, Yang
Abstract: Although metal halide perovskite (MHP) light‐emitting diodes (LEDs) have demonstrated great potential in terms of electroluminescence efficiency, the operational stability of MHP LEDs currently remains the biggest bottleneck toward their practical usage. Well‐confined excitons/charge carriers in a dielectric/quantum well based on conventional spatial or potential confinement approaches substantially enhance radiative recombination in MHPs, but an increased surface‐to‐volume ratio and multiphase interfaces likely result in a high degree of surface or interface defect states, which brings about a critical environmentally/operationally vulnerable point on LED stability. Here, an effective solution is suggested to mitigate such drawbacks using strategically designed surface‐2D/bulk‐3D heterophased MHP nanograins for long‐term‐stable LEDs. The 2D surface‐functionalized MHP renders significantly reduced trap density, environmental stability, and an ion‐migration‐immune surface in addition to a fast radiative recombination owing to its spatially and potentially confined charge carriers, simultaneously. As a result, heterophased MHP LEDs show substantial improvement in operational lifetime ( T 50 : >200 h) compared to conventional pure 3D or quasi‐2D counterparts ( T 50 : < 0.2 h) as well as electroluminescence efficiency (surface‐2D/bulk‐3D: ≈7.70 ph per el% and pure 3D: ≈0.46 ph per el%). Abstract : An effective solution is suggested to mitigate the drawbacks of metal halide perovskite (MHP) using strategically designed surface‐2D/bulk‐3D heterophased MHP nanograins for long‐term‐stable light‐emitting diodes. The 2D surface‐functionalized MHP renders significantly reduced trap density, environmental stability, and an ion‐migration‐immune surface in addition to a fast radiative recombination, simultaneously.